THE HISTORICAL SETTING AND ORIGINAL TRAITS OF THE WORLD CRISIS - François Chesnais (Revista de Políticas Públicas, 2014)
The most dramatic and most publicized episodes of the world crisis have been financial: the subprime mortgage market collapse in 2007, the failure of Lehmann Brothers in September 2008 and more recently the Eurozone banking and sovereign debt crisis. They have of course each time had their own impact on production, trade and employment. But this does not make the crisis a “crisis of financialisation” or of “neoliberalism”, but of capitalism tout court at a given moment of its history. Its underlying causes are overproduction and over-accumulation at world level and an effective play of the tendency of the rate of profit to fall despite the recourse by capital to the offsetting factors. The length of the crisis, which is now named not a US ‘Great Recession” but a global slump (McNally, 2011), and the end of the phase where China and Brazil appeared to be decoupled from the world crisis are expressions of this.